Pemberdayaan Ekonomi Ibu-ibu PKK di Desa Kalisari, Banyumas melalui Pelatihan Needle Felting Limbah Wol - Andrianto, Dimas; Sobari, M Hilmy Rifq; Alexandra, Angelya Cintania; Hazim, Naufal Wildan; Sitanggang, Rianta Faustina; Marfiana, Arila Safa; Yudono, Nur Annisa Windi; Al Malik, Ahmad Fauzan; Walidayyin, Sekar Wangi (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
The economic empowerment for women, members of the empowerment and family welfare (PKK) in Kalisari Village, Banyumas, through wool waste needle felting training is a thematic-real world application of work and study (KKN-T) IPB Innovation 2025. This activity aims to transform the problem of sheep wool waste (approximately 150 kg/year) from local farms into raw materials of economic value, empowering women of Kalisari Village with needle felting skills to create new micro-business opportunities, producing white tofu-shaped key chain dolls as typical village souvenirs, and providing knowledge and skills to participants regarding the economic potential of wool waste and needle felting techniques. The methods were a needle felting lecture and training, held on 24th July 2025 at the Kalisari Village Hall, followed by 30 PKK women, and supported by the Kalisari Village Government, ASF Farm (as a wool supplier), and PKK Kalisari. Evaluation was carried out with a pre-test and post-test to measure the increase in participants' understanding. The main results of this program were a 22% increase in participants' understanding and the production of 13 keychain dolls, establishing a wool supply partnership with ASF Farm, and becoming a regular program of the PKK Kalisari under working group 2. Sustainable program support was provided in the form of equipment and access to video tutorials. In conclusion, this program showed the potential for increasing the economic empowerment of PKK mothers through needle felting production.